Про окремі аспекти співвідношення понять “неправдива інформація”, “фейк”, “оціночні судження” в українському інформаційному просторі - Дяченко, Злата Євгенівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
Along with the development of the information society and modern achievements in the field of information technologies, the Internet is also developing. The Internet, in addition to performing the functions of exchange of opinions and obtaining information by its users in the period of information confrontation, becomes an object and a means of information management. Among the users of this network, there are groups of people or individuals who deliberately spread false or distorted information. That is why the question of determining the legal regime of fakes in Ukraine is gaining considerable relevance. Fakes, or unreliable information, seriously affect public opinion, political processes, and the stability of Ukrainian society as a whole.